Role of Endoscopy in Primary Sclerosing Cholangitis - Bhat, Purnima (Clin Endosc, 2021)
Primary sclerosing cholangitis (PSC) is a progressive disease of the bile ducts that usually results in chronic liver disease often requiring liver transplantation. Endoscopy remains crucial to the care of these patients, although magnetic resonance cholangiopancreatography has replaced endoscopic retrograde cholangiopancreatography (ERCP) as the primary imaging modality for diagnosis. For detection of dysplasia or cholangiocarcinoma, ERCP with intraductal sampling remains compulsory. Moreover, dominant strictures play an important part in the disease development, and management by balloon dilatation or stenting could contribute to long-term prognosis. In addition, endoscopy offers management for adverse events such as bile leaks and anastomotic strictures after liver transplantation. Finally, the special phenotype of inflammatory bowel disease associated with PSC as well as the frequent occurrence of portal hypertension mandates close follow-up with colonoscopy and upper endoscopy. With the emergence of novel techniques, the endoscopist remains a key member of the multidisciplinary team caring for PSC patients.